Multicentre evaluation of the Boehringer Mannheim/Hitachi 917 analysis system. Issue 3 (2000) - van Suijlen, Jeroen D. E.; Blijenberg, Bert G.; Hofmann, Jörg; Bauer, Kurt; Zaman, Zahur; Blanckaert, Norbert; Degenhard, Peter; Wielckens, Klaus; Ferré, Carmen; Torralba, Antonio; Martyn, Mary; Kelly, Anne; et al.
Abstract : The new selective access analysis system BM/Hitachi 917 was evaluated in an international multicentre study, mainly according to the ECCLS protocol for the evaluation of analysers in clinical chemistry. Forty-three different analytes, covering 56 different methods enzymes, substrates, electrolytes, specific proteins, drugs and urine applications were tested in seven European clinical chemistry laboratories. Additionally, the practicability of the BM/ Hitachi 917 was tested according to a standardized questionnaire. Within-run CVs (median of 3 days) for enzymes, substrates and electrolytes were <2% except for creatine-kinase MB isoform and lipase at low concentration. For proteins, drugs and urine analytes the within-run CVs were < 4% except for digoxin and albumin in urine. Between-day median CVs were generally < 3% for enzymes, substrates and electrolytes, and < 6% for proteins, drugs and urine analytes, except for lipase, creatine kinase and MB isoform, D-dimer, glycosylated haemoglobin, rheumatoid factors, digoxin, digitoxin, theophylline and albumin in urine in some materials. Linearity was found according to the test specifications or better and there were no relevant effects seen in drift and carry-over testing. The interference results clearly show that also for the BM/Hitachi 917 interference exists sometimes, as could be expected because of the chemistries applied. It is a situation that can be found in equivalent analysers as well. The accuracy is acceptable regarding a 95–105% recovery in standard reference material, with the exception of the creatinine Jaffé method. Most of the 160 method comparisons showed acceptable agreement according to our criteria: enzymes, substrates, urine analytes deviation of slope ± 5%, electrolytes ± 3%, and proteins and drugs ± 10%. The assessment of practicability for 14 groups of attributes resulted in a grading of one–three scores better for the BM/Hitachi 917 than the present laboratory situation. In conclusion, the results of the study showed good analytical performance and confirmed the usefulness of the system as a consolidated workstation in medium-sized to large clinical chemistry laboratories.